Pengembangan Bi’ah Lughawiyah Maharah Al-Kalam Bahasa Arab bagi Mahasiswa dan Dosen di Prodi PBA UNM - Raudatussolihah, Baiq; Fathurrahman, Ali; Kholida, Masita Taufiqi; Rais. TM, Ahmad; Perdana, Dyah Adila (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
Abstract: This article discusses the development of bi’ah lughawiyah as a strategy to strengthen maharah al-kalam for students and lecturers of the Arabic Language Education Study Program (PBA) of Makassar State University (UNM). The background of this research is the need to create a conducive Arabic language environment to encourage communicative speaking skills, both in academic and non-academic contexts. The method used is a descriptive conceptual approach with analysis and enrichment of initial observation results in the PBA UNM environment. The results of the study indicate that the development of bi’ah lughawiyah is effective if designed through three ecological layers: 1) the micro level in the form of task-based language teaching in the classroom and the use of targeted translanguaging, 2) the meso level in the form of co-curricular activities such as Arabic Day, debate clubs, and Lughah Corner, and 3) the macro level in the form of study program policies that regulate the use of Arabic among lecturers. This model is able to improve students’ fluency, accuracy, and confidence, while strengthening lecturers’ competence. This article emphasizes that the development of bi'ah lughawiyah is not only cultural, but also strategic in building an academic culture and developing the maharah al-kalam of Arabic at PBA UNM.